On \(\hat{\hat{{g}}}\)-Closed Sets in Fuzzy Topological Spaces - Deepika, P.; Rameshpandi, M.; Premkumar, R. (Communications in Mathematics and Applications, 2021)
In this paper, we introduce the concepts of fuzzy \(\hat{\hat{g}}\)-closed sets and fuzzy \(\hat{\hat{g}}\)-open sets. Further, we study some of their properties.